Airborne electromagnetic data levelling based on inequality-constrained polynomial fitting. Issue 5 (2nd September 2020) - Zhu, Kaiguang; Zhang, Qiong; Peng, Cong; Wang, Hao; Lu, Yiming
Abstract : We have developed a novel technique for airborne time-domain electromagnetic data levelling using inequality-constrained polynomial fitting. In the approach, channel data of a certain survey area are levelled under the constraint of off-time attenuation rule. Based on the correlations between flight lines, Huang has proposed that level errors could be fitted by the differences between the flight line data and its reference line data. Thus, the level errors represented as polynomial functions are determined by the least-squares algorithm subjecting to the constraint of the adjacent channel. In addition, only the survey area data in the absence of anomalous features are used in the levelling process to avoid fake level problem. We validate the levelling method by applying it to synthetic data and field data, comparing with line-to-line correlation levelling.